The Impact of Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Total Asset Turnover Towards The Profit Changes Of Mining Companies Listed On Indonesia Stock Exchange Period 2016-2018 - Tommy Minggus; Mohammad Wasil; I. G. A. Aju Nitya Dharmani (Quantitative Economics and Management Studies, 2020)
This study aims to determine whether CR, DER, NPM, and TATO effect profit changes. The population in this research are mining companies listed in the Indonesia Stock Exchange period 2016-2018 consisting of 48 companies. Sampling was done by purposive sampling and 15 companies were selected. The data in the study comes from the secondary data obtained through the documentation technique. Data analysis with multiple regression analysis using SPSS for Windows version 18. The results showed that there was significant influence simultaneously between CR, DER, NPM, and TATO to Profit Changes. Based on the partial test, the conclusion CR and TATO has positive and not significant effect on profit changes. DER has negative and not significant effect in profit changes. NPM has positive and significant effect on profit changes.